Developing the Eighth Graders' Digital Writing Material Book Using Book Creator Application - Trima Niat Telaumbanua, Nita; Harefa, Afore Tahir; Laoli, Adieli; Zega, Riswan (JLE: Journal of Literate of English Education Study Program, 2025)
In response to the transformation of education in the digital era and the implementation of Kurikulum Merdeka, this study aims to develop digital writing materials using Book Creator for eighth grade students at SMP Swasta Kristen BNKP Gunungsitoli. This research seeks to identify the level of appropriateness of the developed digital writing materials and to evaluate how effectively these materials support students’ writing skills. The study employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The result of this study is an interactive digital book titled Interactive Writing for Creative Thinkers, which was developed to address students’ writing challenges and to enhance their engagement, creativity, and digital literacy. The findings from the pre-test and post-test demonstrated a significant improvement in students’ writing skills, particularly in the areas of vocabulary, sentence structure, and writing mechanics. Additionally, student evaluations indicated highly positive perceptions regarding the book’s ease of use, interactivity, and content relevance, further supporting its appropriateness for classroom implementation. Overall, the study confirms that contextually designed digital teaching materials, which are aligned with students’ actual learning needs, are not only appropriate for use in the classroom but also essential in promoting active learning and meeting the demands of 21st-century education.